A statistical analysis of wind energy potential in Ibadan, Nigeria, based on weibull distribution function (2008)
Modeling of wind speed variation is an essential requirement in the estimation of the wind energy potential for a typical site. In this paper, the wind energy potential in Ibadan (Lat. 7.43°N; Long. 3.9°E; Alt. 227.2m) is statistically analyzed using daily wind speed data for 10 years (1995-2004) obtained from the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria. The daily, monthly, seasonal, and yearly wind speed probability density distributions are modeled using Weibull Distribution Function. The measured annual mean wind speed in Ibadan is 2.75 ms-1, while mean wind speed and the power density predicted by the Weibull probability density function are 2.947 m/s and 15.484 Wm-2, respectively. Ibadan can be classified as a low wind energy region. The coefficient of determination (R2) between the actual wind speeds and the Weibull predicted values ranged between 0.475 - 0.792. The Weibull distribution function can be used with acceptable accuracy for prediction of wind energy output required for preliminary design and assessment of wind power plants.